Teriparatide as a nonoperative treatment for tibial and femoral fracture nonunion: A case report. Issue 16 (April 2017) - Xiaofeng, Li; Daxia, Xu; Yunzhen, Chen
Abstract: Rationale: Fracture nonunion is a great challenge for orthopedic surgeons. Many surgical interventions are associated with significant pain and heavy economic burden. Therefore, our aim was to evaluate the outcomes of a new nonoperative treatment for fracture nonunion. Patient concerns: A 44-year-old man suffered closed fractures of the right tibia and left femur. Eleven months after surgery, there was no radiographic healing between fracture fragments. Diagnoses: Fracture nonunion of the right tibia and left femur. Interventions: The patient received systemic treatment with teriparatide (recombinant human Parathyroid Hormone 1–34) 20 μg/d for 8 months, with further observation at 4 months after discontinuation. During treatment, bone metabolic markers were measured to evaluate metabolic activity of osteoblasts and osteoclasts. The Ethics Committee of Qilu Hospital of Shandong University approved this study. Outcomes: Satisfactory healing of fracture nonunion was obtained without further intervention. Lessons: Anabolic treatment with teriparatide showed a positive effect on healing of fracture nonunion. Evaluation of bone metabolic markers during treatment is necessary to observe the curative effect. In view of the positive effect of teriparatide on healing of fracture nonunion in numerous animal models and clinical studies, it may be a promising alternative treatment for fracture nonunion in patients who are not suitable for surgical intervention.